2015
DOI: 10.1159/000442970
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Findings in Anterior Chamber Ointment Globule after Phacoemulsification

Abstract: We present 2 cases of anterior chamber ointment with evidence of progressive endothelial cell loss. In both cases, an anterior segment optical coherence tomography (OCT) was similar to an OCT of a tobramycin-dexamethasone ointment placed on a pen tip. An anterior segment OCT also demonstrated the direct contact of the globule with the corneal endothelium. A gas chromatography/mass spectrometry analysis documented the similarity to tobramycin-dexamethasone ointment in 1 case. Anterior segment OCT can help in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Our patient presented 33 months after cataract surgery with CME and an AC mass consistent with ointment. Though chromatography was unavailable, the operative note indicated that Maxitrol ointment was placed at the conclusion of surgery, and the appearance on exam is identical to previous reports [4, 5, 7]. This is one of the longest durations that Maxitrol ointment has been left inside the AC, causing ocular toxicity evidenced by CME and decreased endothelial cell count.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our patient presented 33 months after cataract surgery with CME and an AC mass consistent with ointment. Though chromatography was unavailable, the operative note indicated that Maxitrol ointment was placed at the conclusion of surgery, and the appearance on exam is identical to previous reports [4, 5, 7]. This is one of the longest durations that Maxitrol ointment has been left inside the AC, causing ocular toxicity evidenced by CME and decreased endothelial cell count.…”
Section: Discussionsupporting
confidence: 76%
“…A globule of intraocular chloramphenicol ointment has been observed for 6 years inside a patient's AC before the development of CME necessitating AC washout [4]. Some patients with ointment in the AC also develop corneal endothelial cell loss [5]. In another case where Maxitrol ointment remained in the AC for 2 years, a patient developed anterior uveitis and elevated IOP, but without CME and with normal endothelial cell count [6].…”
Section: Discussionmentioning
confidence: 99%